Design, Synthesis, Biological Evaluation, and Molecular Docking Study of 4,6-Dimethyl-5-aryl/alkyl-2-[2-hydroxy-3-(4-substituted-1-piperazinyl)propyl]pyrrolo[3,4-c]pyrrole-1,3(2H,5H)-diones as Anti-Inflammatory Agents with Dual Inhibition of COX and LOX - Aleksandra Redzicka; Benita Wiatrak; Izabela Jęśkowiak-Kossakowska; Andrzej Kochel; Remigiusz Płaczek; Żaneta Czyżnikowska (Pharmaceuticals, 2023)
In the present study, we characterize the biological activity of a newly designed and synthesized series of 15 compounds 2-[2-hydroxy-3-(4-substituted-1-piperazinyl)propyl] derivatives of pyrrolo[3,4-c]pyrrole 3a–3o. The compounds were obtained with good yields of pyrrolo[3,4-c]pyrrole scaffold 2a–2c with secondary amines in C2H5OH. The chemical structures of the compounds were characterized by 1H-NMR, 13C-NMR, FT-IR, and MS. All the new compounds were investigated for their potencies to inhibit the activity of three enzymes, i.e., COX-1, COX-2, and LOX, by a colorimetric inhibitor screening assay. In order to analyze the structural basis of interactions between the ligands and cyclooxygenase/lipooxygenase, experimental data were supported by the results of molecular docking simulations. The data indicate that all of the tested compounds influence the activity of COX-1, COX-2, and LOX.